Diatom diversity in headwaters influenced by permafrost thawing: first evidence from the Central Italian Alps - Rotta, F.; Cerasino, L.; Occhipinti-Ambrogi, A.; Rogora, M.; Seppi, R.; Tolotti, M. (Advances in Oceanography and Limnology, 2018)
Glacier melting and permafrost thawing are the most evident effects of the current climate change that is strongly affecting high mountain areas, including the European Alps. As the thawing rate of subsurface ice is lower than for glacier ice, it is expected that, while glaciers retreat, an increasing number of Alpine headwaters will become more influenced by permafrost degradation during the 21st century. Despite the expected change in the relative importance of glacier and permafrost in determining Alpine hydrology, studies addressing effects of permafrost thawing on chemical and, especially, biological features of adjacent surface waters are still scarce. The present study contributes to characterise the epilithic and epiphytic diatom diversity in a set of permafrost-fed headwaters in three subcatchments differing in bedrock lithology of the Italian Central Alps (Trentino Alto-Adige) in relation to water chemistry and habitat features. In addition, it explores chemical and biological differences between permafrost-fed streams and headwaters with no direct contact to permafrost, namely glacier-fed (kryal) and precipitation-/groundwater-fed (rhithral) streams. Permafrost-fed waters showed higher electrical conductivity and enhanced ion concentrations than glacier- and precipitation-fed waters, while concentration of trace elements (e.g. Sr, Ni, Zn, As) were more irregularly distributed among waters of different origin, though they showed a tendency to reach higher levels in permafrost-fed waters. Diatom species richness and diversity were lower in permafrost-fed headwaters, and were principally related to water pH and trace metal concentrations. Epiphytic diatom assemblages were more diverse than epilithic ones, independently from the water origin, while differences in species composition were not sufficient to unequivocally identify a typical diatom composition for the different water types considered in this study